ENGLISH BEYOND THE CLASSROOM WALL AMONG INDONESIAN COLLEGE STUDENTS OF ENGLISH - Darwanto, Agus; Rini, Sri Endah Setia; Herusatoto, Hesthi (Conscientia - Journal on Language, Literature, and Culture, 2023)
This research was to find out patterns of speaking English activities among Indonesian learners of English. This is to find out their lacks, needs, and wants regarding out-of-class English activities to improve their speaking English proficiency when in an EFL (English as a Foreign Language) context like Indonesia. As many as 107 respondents of college students of English of 4 universities in Indonesia participated in this research by responding to closed and open items provided in questionnaires. After a deep descriptive qualitative analysis, results show that most respondents perceived that they lacks peaking skills amongst other English skills. They lack chances to speak the language. They wanted to have ample extramural activities to practice speaking English. They needed to be “forced” to venture to speak English when outside classroom. In conclusion, there is a discrepancy (lacks) between the ideal proficiency that they perceived and the current level of speaking skills. They need to be provided with learning policies to provide them with chances events or venues to practice speaking English. Extramural speaking activities need to be explored and then written into a school policy so that students will not only speak English when in class but also when outside classes. Participatory-yet-mandatory extramural English activities need to be promoted.